Language policies as key aspect of migration policies: an evolving scenario in Europe - Lorenzo Rocca (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave)
The article focuses on the role of language policies within the broader framework of migration policies in Council of Europe Member States. A description of the system currently in place in a representative sample of countries will lead to considerations related to language requirements, including the linguistic dimension of the knowledge of society requirements, as well as to language learning opportunities, where present.